2005
DOI: 10.1007/s00425-005-1481-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cell wall polysaccharides in developing barley (Hordeum vulgare) coleoptiles

Abstract: Cell wall polysaccharides in developing barley coleoptiles were examined using acetic acid-nitric acid extraction, alditol acetate and methylation analyses and enzymatic digestion. The coleoptile cell wall from imbibed grain was rich in pectic polysaccharides (30 mol%), arabinoxylan (25 mol%), cellulose (25 mol%) and xyloglucan (6 mol%), but contained only low levels of (1-->3,1-->4)-beta-D-glucan (1 mol%). During 5 days of coleoptile growth, pectic polysaccharides decreased steadily to about 9 mol%, while (1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
188
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 189 publications
(199 citation statements)
references
References 65 publications
8
188
1
2
Order By: Relevance
“…5). The peak in HvCslF6 transcript abundance at 4 to 5 d after germination corresponds to the time when elongation of the coleoptile ceases, the leaf breaks out of the coleoptile, and maturation of the coleoptile begins (Gibeaut et al, 2005). It also corresponds to the time at which levels of (1,3;1,4)-b-D-glucan peak in coleoptiles, at about 10 mol % of the walls (Gibeaut et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5). The peak in HvCslF6 transcript abundance at 4 to 5 d after germination corresponds to the time when elongation of the coleoptile ceases, the leaf breaks out of the coleoptile, and maturation of the coleoptile begins (Gibeaut et al, 2005). It also corresponds to the time at which levels of (1,3;1,4)-b-D-glucan peak in coleoptiles, at about 10 mol % of the walls (Gibeaut et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The tissue series cDNAs used for Q-PCR were prepared as described by Burton et al (2004). The RNA extracts from coleoptiles were prepared from young seedlings grown in vermiculite in the dark at room temperature (Gibeaut et al, 2005). Coleoptiles were dissected away from seedling leaves 1 to 7 d after imbibition of the grain.…”
Section: Plant Materialsmentioning
confidence: 99%
“…The reason why xyloglucan is only temporarily deposited during endosperm cellularization is unknown but, like callose, it is a polysaccharide that is laid down early in phragmoplast formation and is subsequently removed (Samuels et al, 1995;Staehelin, 2000a, 2000b;Otegui et al, 2001), presumably because other polysaccharide(s) supersede its role later in development. Although a definitive role for xyloglucan during early development cannot be deduced from this study, it is of interest that the low levels of xyloglucan often seen in the cell walls of the commelinoid monocots appears to be associated with young and/or expanding cells, although xyloglucan is present in the mature endosperm cell walls of rice (Kato et al, 1982;Nevins, 1984, 1991;Gibeaut et al, 2005) and has recently been reported to be present in mature tissues of specific cell types in some members of the Poales (Brennan and Harris, 2011). Cocuron et al (2007) proposed that the CSLC proteins function is to synthesize the xyloglucan backbone although Dwivany et al (2009) have also proposed a role for some CSLC family members in the synthesis of cellulose in certain specialized cell types.…”
Section: Xyloglucanmentioning
confidence: 90%
“…Sequences encoding XTHs are surprisingly abundant in barley EST data bases, given the relatively low levels of xyloglucans in walls of most barley tissues (23,32). There are at least 22 XTH genes in barley (23), about 30 in rice (33), about 40 in Populus trichocarpa (34), and about 33 in Arabidopsis (35).…”
Section: Discussionmentioning
confidence: 99%